Application of the Canadian CT head rules in managing minor head injuries in a UK emergency department: implications for the implementation of the NICE guidelines. Issue 4 (18th June 2004) - Sultan, H Y; Boyle, A; Pereira, M; Antoun, N; Maimaris, C
Abstract : Objective: : In 2002 a new protocol was introduced based on the Canadian CT rules. Before this the Royal College of Surgeons "Galasko" report guidelines had been followed. This study evaluates the effects of the protocol and discusses the impact of the implementation of the NICE head injury guidelines—also based on the Canadian CT rules. Methods: A "before and after" study was undertaken, using data from accident and emergency cards and hospital notes of adult patients with head injuries presenting to the emergency department over seven months in 2001 and nine months in 2002. The two groups were compared to see how rates of computed tomography (CT), admission for observation, discharge, and skull radiography had changed after introduction of the protocol. Results: : Head CT rates in patients with minor head injuries (MHI) increased significantly from 47 of 330 (14%) to 58 of 267 (20%) (p<0.05). There were also significantly increased rates of admission for observation, from 111 (34%) to 119 (45%). Skull radiography rates fell considerably from 33% of all patients with head injuries in 2001 to 1.6% in 2002, without any adverse effect. Conclusions: This study shows that it is possible to replace the current practice in the UK of risk stratification of adult MHI based on skull radiography, with slightly modified versions of the Canadian CT rule/NICE guidelines. This will result in a large reduction in skull radiography and will be associated with modest increases in CT and admissions rates. If introduction of the NICE guideline is to be realistic, the study suggests that it will not be cost neutral.